The Effects of Video Materials on English-Major Students’ Learning: A Test of Hypotheses in the Vietnamese Context - Ho, Thanh Vy; Le, Thanh Thao (Faculty of Education and Teacher Training of IAIN Palopo, 2022)
Video materials are used more frequently in English as a foreign language (EFL) classes since they are perceived to be effective. However, using video materials is challenging because it requires EFL teachers’ abilities to determine the videos' suitability for their learners. As a result, this study was conducted qualitatively to listen to language learners’ voices about using video materials in their English classes. There were six hypotheses related to the use of video materials in the Vietnamese context. Fine focus-group interviews were organized to collect data from 25 English students learning in a tertiary institution in the Mekong Delta of Vietnam. The data revealed that Vietnamese students perceived using video materials to be effective. The animated videos with beautiful sounds helped improve their learning motivation. Regarding the existence of video materials on various online platforms, the students could learn outside the classroom as well as increase their learner autonomy. However, to integrate video materials into classroom activities, English teachers were required to have sufficient abilities to choose the appropriate videos for their learners. As a result, the study proposed several practical implications for educators who would like to use video materials in their classrooms.